2018
DOI: 10.3389/fpsyt.2018.00039
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention and a Direction of Novel Therapeutics for the Improvement of Functional Outcomes in Schizophrenia: A Selective Review

Abstract: BackgroundA recent review reported that the median proportion of patients recovering from schizophrenia was 13.5% and that this did not change over time. Various factors including the duration of untreated psychosis, cognitive impairment, negative symptoms, and morphological changes in the brain influence the functional outcome of schizophrenia. The authors herein reviewed morphological changes in the brain of schizophrenia patients, effects of early intervention, and a direction of developing novel therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 119 publications
(142 reference statements)
1
10
0
Order By: Relevance
“…98 Taken together with the findings from other groups, 11 our results suggest a period of intense gray matter reduction during the early phases of schizophrenia, especially in the lateral temporal and insular regions, which is likely to underlie the severity and early course of clinical symptoms in a region-specific manner but could be ameliorated with antipsychotic medication. Given that the STG, which includes the primary auditory and neocortical language regions, 99 is also involved in social cognition in concert with the insular cortex, a component of the limbic integration cortex, and other limbic © 2018 The Authors Psychiatry and Clinical Neurosciences © 2018 Japanese Society of Psychiatry and Neurology regions, 100,101 these longitudinal findings are in line with a hypothesized perisylvian pathology of schizophrenia 37 where excessive dopamine transmission in the STG and insula causes positive symptoms (e.g., delusions, hallucinations, and disorganized speech) that are responsive to antipsychotic treatment. However, it is also reported that higher doses of antipsychotics (especially typical ones) may contribute to more progressive gray matter loss in schizophrenia.…”
Section: Progressive Changes After Onsetmentioning
confidence: 74%
See 4 more Smart Citations
“…98 Taken together with the findings from other groups, 11 our results suggest a period of intense gray matter reduction during the early phases of schizophrenia, especially in the lateral temporal and insular regions, which is likely to underlie the severity and early course of clinical symptoms in a region-specific manner but could be ameliorated with antipsychotic medication. Given that the STG, which includes the primary auditory and neocortical language regions, 99 is also involved in social cognition in concert with the insular cortex, a component of the limbic integration cortex, and other limbic © 2018 The Authors Psychiatry and Clinical Neurosciences © 2018 Japanese Society of Psychiatry and Neurology regions, 100,101 these longitudinal findings are in line with a hypothesized perisylvian pathology of schizophrenia 37 where excessive dopamine transmission in the STG and insula causes positive symptoms (e.g., delusions, hallucinations, and disorganized speech) that are responsive to antipsychotic treatment. However, it is also reported that higher doses of antipsychotics (especially typical ones) may contribute to more progressive gray matter loss in schizophrenia.…”
Section: Progressive Changes After Onsetmentioning
confidence: 74%
“…Glutamatergic excess due to hypofunction of the N ‐methyl‐ d ‐aspartate receptors on corticolimbic gamma‐aminobutyric acidergic interneurons may also lead to adverse neurotoxic effects in the early stages of psychosis . While these potential mechanisms may partly explain histological changes observed in the cortical regions of schizophrenia patients, such as decreased numbers of parvalbumin‐positive interneurons and dendritic spines of pyramidal neurons (see review by Kurachi et al …”
Section: Mri Findings In Schizophreniamentioning
confidence: 99%
See 3 more Smart Citations